Hydrovise: A non-proprietary open-source software for hydrologic model and data visualization and evaluation. (December 2020) - Jadidoleslam, Navid; Goska, Radoslaw; Mantilla, Ricardo; Krajewski, Witold F.
Abstract: The authors developed a non-proprietary web-browser based open-source software that allows users to visualize and evaluate hydrologic space-time data in an interactive environment. Hydrovise is client-side browser-based software that interprets a configuration file to construct control elements in the Graphical User Interface for visualizations of space-time data and model simulation evaluations. It leverages the concept of three-dimensional data cubes that facilitate query in space, time, and variable dimension(s) without the requirement for a database system. Using a configuration file, users can define data sources as local file system resources and or external data sources (e.g., online data services). This capability makes Hydrovise a flexible and portable solution where users can share their hydrologic data in an interactive web environment. This paper provides the software description with four distinct example use cases including, but not limited to, time-series data visualization and evaluation, grid-based and river network-based data visualizations. Highlights: We developed a client-side web-browser based software to lower code barrier for hydrologic data visualization and evaluations. Hydrovise uses a configuration file to generate a flexible and customizable graphical user interface dynamically. The data model leverages space-time-variable data cubes to relax the requirement for a database system. Example use cases include real-time streamflow data browser, and hydrologic model performance evaluations and visualizations. Target audience are graduate students, research scientists, and decision-makers with limited expertise in web development.